A pathway to change - Kristjanson, Patricia M.; Le Borgne, Ewen (2012)
People and communities can be amazingly resourceful and innovative when adjusting to change, yet the challenges today are hugely complex. How can we work together to make the changes needed if we are to feed 9 billion people while taking care of the environment?